EFFECTIVENESS OF BOTANICAL PESTICIDES AGAINST FALL ARMYWORM PESTS (Spodoptera frugiperda) ON RICE PLANTS - Gusriadi, Gusriadi; Muhanniah, Muhanniah; Thamrin, Nining Triani (J-PEN Borneo : Jurnal Ilmu Pertanian, 2023)
Spodoptera frugiperda pests attack many food crops, including rice plants. Their larval life stage destroys rice plants and cause crop failure due to the attack rate, which can lead to yield losses of up to 80%. The study aimed to determine the effectiveness of botanical pesticides against fall armyworm pests and determine the concentration of botanical pesticides that are most appropriate to be used to control fall armyworm pest populations on rice plants. This research was conducted from May to July 2023 in the experimental land of Tonrong Rijang Village, Kacamatan Baranti, Sidrap Regency. The treatment of this study is P0 (control), P1 (100 ml botanical pesticide + 100 ml liquid soap + 800 ml water), P2 (300 ml botanical pesticide + 100 ml + 600 ml water), P3 (500 ml botanical pesticide + 100 ml liquid soap), P4 (700 ml botanical pesticide + 100 ml liquid soap + 200 ml water). The results showed that the application of botanical pesticides had an intangible influence on fall armyworm pests on rice plants due to the rain factor, which resulted in botanical pesticides being washed off, causing the application dose to be less than pestimal. The highest fall armyworm pest attack mortality at P4 is with an average of 100%, and the application of P1 doses shows the highest average attack intensity of 48.47% with a medium-scale damage category, this is because if the concentration of botanical pesticides is getting smaller, the intensity of fall armyworm pest attacks that occur on plants is also high.